Study of Some Structural and Optical Properties for Synthesized Graphene/Polyaniline/Zns Nanocomposite - Salman, Elaf Kareem; Muhammed, Ghaida Salman (Iraqi Journal of Physics, 2024)
Hybrid graphene (GR)/ polyaniline (PANI) based composites incorporating zinc sulfide (ZnS) nanoparticles were synthesized using the drop-casting method. The weight percentage of ZnS was varied from 0.01 to 0.05%. The optical, structural, and morphological characteristics of the nanocomposite were examined utilizing  X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Atomic Force Microscopic (AFM), and UV-Vis spectroscopy. The qualities and dimensions of the GR, PANI, and  ZnS NPs and nanoparticle morphology resulting from the nanocomposite process were examined. Utilizing energy dispersive energy X-ray dispersive (EDX), the weight percentage of each element can be verified. The widening sharp peaks in the XRD patterns suggested the creation of a nanocrystalline phase of ZnS with a crystallite size of less than 50 nm. SEM demonstrated the interaction between ZnS nanoparticles and graphene/polyaniline. Surface topography examination using AFM shows that ZnS NPs may be effectively dispersed on top of GR/PANI structures. The ultraviolet-visible absorption spectrum (UV-Vis) showed a small absorption peak at the wavelength of 459.34nm and a broad absorption peak at 652nm.